‘What Else About Her Is Fake?’: ‘Emphasised’ Femininity, Authenticity and Appearance - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
This chapter charts the ways in which young women’s negotiations of dress in the NTE are shaped by notions of visibility and authenticity and also by class. I explore the ways in which an exaggerated or emphasised mode of femininity is normalised to an extent within the NTE and highlight some of the pleasures and values young women found in their negotiations of femininity through dress, whether wholeheartedly embracing or ‘flashing’ femininity. Tensions and ambivalences are exposed as the participants both adopted and resisted elements of ‘girly’ and ‘tomboy’ identities. I then explore the ways in which forms of classed othering function to construct the feminine self in contrast to those who are perceived to lack the taste and resources to ‘do’ femininity appropriately and instead embody a somehow inauthentic and overdone performance of femininity. I briefly consider the intersections between hyper-feminine and ‘slutty’ dress, and finally explore how attempts by working-class young women to resignify a more excessive look as ‘glamorous’ may be mocked and judged beyond the local context.
Keywords: Essex Girl; Geordie; Girly Girl; Tomboy; clothingClothing

Carefree or Controlled? Understanding the Night-Time Economy - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
The term ‘Night-Time Economy’ was coined in the late twentieth century (Shaw 2014) in town planning circles, and increasingly used into the twenty-first century to describe the expanding number of pubs, bars and clubs concentrated in city centres and targeting predominantly 18–24-year-olds (Roberts 2006: 332). But what exactly is the Night-Time Economy, and what role does it play in the lives of young women today? How has it changed as a site of leisure, and what does it mean to say that neoliberal forces have played a role in shaping it? What do we mean by the supposed ‘feminisation’ of the NTE, and what are the implications of this process for the ways that women engage with these spaces? This chapter charts the development of the NTE in the UK and the rise of the ‘24-hour city’, highlighting the ways in which neoliberal ideals have shaped both the landscape of the NTE and the types of behaviours and consumption practices that are expected within it. Such considerations are important for research that attends both to the wider social structures within the NTE and the individual specificities of the lives of young people as they participate in it. I will then explore the significance of space and place in research focusing on the NTE, situating the current study geographically and exploring Newcastle’s own NTE in more depth and detail.
Keywords: Charvis; Essex Girl; Geordie; Night-time Economy; Northern Identity